Asymmetric Michael Addition of Oxindoles to Allenoate Catalyzed by N‐Acyl Aminophosphine: Construction of Functionalized Oxindoles with Quaternary Stereogenic Center. Issue 2 (8th January 2014) - Chen, Jinhao; Cai, Yuepeng; Zhao, Gang
Abstract A novel reaction between ethyl allenoate and oxindoles that enables the asymmetric synthesis of 3, 3‐bisubstituted oxindoles with our previously established bifunctional N‐acyl aminophosphine catalysts is reported. These products bearing a chiral quaternary carbon center at the C‐3 position of the oxindoles may have potential significance in the synthesis of related structures. The best performance of these processes provides adducts with 92% yield and 94% ee. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>